Pengaruh Penambahan Spirulina platensis sebagai Sumber Protein Nabati pada Daging Analog bagi Vegetarian - Sari, Berliana Luckyta; Dewi, Eko Nurcahya; Fahmi, Ahmad Suheli (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
Spirulina platensis is a vegetable protein source that may improve the quality of food product. The objective of this study was to determine the effect of addition S. platensis on analog meat at concentrations of 0, 10, 20, and 30% and to determine the best concentration of addition S. platensis on meat analogs preferred by the panelists. The processing of meat analogs used steaming method at 100°C for 30 minutes. The researched method applied a completely randomized design. The analog meat samples were analyzed in terms of protein content, protein digestibility, moisture content, texture, color, and hedonic tests. The highest protein content and protein digestibility was at concentrations of S. platensis 30%, 32.24 and 62%. The moisture content obtained at 30% concentration was 54.70%, and the texture at 30% concentration was 1.53 N which resembles the texture of animal meat. Analog meat preferred by panelist was at concentration of 20% which had a texture preference of score of 6.33; aroma 5.00 and taste 6.33 from the average 30 panelist score and had a confidence interval value of 5.56<µ<6.22.